Military-technological innovation in small states: the cases of Israel and Singapore - Bitzinger, Richard A. (2022)
Both Israel and Singapore engage in military-technological innovation in areas deemed critical to strategic sovereignty. Both countries have consistently championed high levels of funding for military R&D and for maintaining and nurturing indigenous defense industries. Both countries have, to a varying degree, also strongly supported the cultivation of local S&T, including the spin-on of commercial high-technology breakthroughs into the defense sector. Israel has been more successful when it comes to military-technological innovation, mostly because it has to: its strategic situation is much more tenuous than Singapore’s. Singapore, on the other hand, faces much less of an existential threat, and so its military-technological innovation activities are more one of desire than necessity.